How to make equity practical in primary schools? Lessons learned in collaborative action research in an educational research lab - Gaikhorst, Lisa; van Caem, Saskia; Edzes, Hester; Snoek, Marco; Volman, Monique (Frontiers in Education, 2025)
IntroductionTo bridge the gap between educational research and practice, grants have been made available in the Netherlands for partnerships of schools and universities to engage in practice-based research. This enabled the establishment of an Educational Research Lab Amsterdam (ERLA), for which its founders, also the authors of this paper, chose diversity and equity as a focus. We wanted to strengthen the agency of teachers and researchers to contribute to social justice, through collaboratively designing and evaluating educational approaches that address diversity and equity challenges in classrooms and schools. In this paper, we discuss (1) how our approach evolved; (2) how it promoted agency in relation to diversity and equity; (3) the challenges we encountered and the lessons we learned.MethodsWe present our reflections as a case study of the ERLA, basing our analysis on (1) documents about our approach; (2) minutes of meetings; (3) reports for funding agencies; (4) notes and e-mails; (5) teacher interviews and questionnaires from ERLA-projects; (6) research proposals, reports, publications. Data were thematically analysed, using the three research questions and eight previously developed principles for collaborative research approaches as lenses.FindingsThe ERLA has developed a functioning structure with school-based learning teams and cross-school thematic teams, supported by researchers. The outputs are useful educational approaches to promote equity in schools, concrete tools, professional development for teachers and school leaders, strengthened school board policies, and scientific publications. Along the way, we gained valuable insights about teacher-researcher collaboration: collective agency is achieved when participants contribute from their area of expertise; it involves struggle and requires negotiation; working structures facilitate agency and should be regularly evaluated; a shared vision on approach and object of the collaboration must be actively maintained, e.g., to uphold principles, and with a view to transparency for external partners.DiscussionThis study provides insights into teacher–researcher collaboration within ERLA, contributing a practice-based perspective to the existing Research Practice Partnerships (RPPs) literature and offering lessons for fostering successful partnerships, such as the importance of recognizing differences in expertise and of a shared vision that is actively maintained and revisited.